Disk-halo interactions: molecular clouds in the Galactic center. Issue Volume 9:Issue S303(2013) (22nd May 2014) - Riquelme, D.; Martín-Pintado, J.; Mauersberger, R.; Martín, S.; Bronfman, L.
Abstract: We study the disk-halo interaction, in the context of orbits and Giant Molecular loops (GMLs) in the Galactic center (GC) region. From a large scale survey of the central kpc of the Galaxy, in SiO J = (2 − 1), HCO + J = (1 − 0) and H 13 CO + J = (1 − 0) molecular emission, we identify shock regions traced by the enhancement of the SiO. These positions were studied using the 12 C/ 13 C isotopic ratio to trace gas accretion/ejection. We found a systematically higher 12 C/ 13 C isotopic ratio (> 40) toward the GMLs and the x 1 orbits than for the GC standard molecular clouds (20–25). The high isotopic ratios are consistent with the accretion of the gas from the halo and from the outskirts of the Galactic disk. From multi-transitional observations of NH3, we derive two kinetic temperature regimes (one warm at ∼150 K and one cold at ∼40 K) for all the positions, except for the GMLs positions where only the warm component is present. The fractional abundances derived from the different molecules support the shock origin for the heating mechanism in the GC. We also present a detailed study of one molecular cloud placed in the foot points of two giant molecular loops, where two of the previously selected positions are placed. Using the 22m Mopra telescope we mapped the molecular cloud M − 3.8 + 0.9 in 3-mm molecular lines. The data show structures at small scale in SiO emission, with narrower line profiles than those of, e.g, HCO + or HCN, which indicate that the shocks are dynamically confined. The data also show clear differences between different molecular tracers, e.g., between the SiO and HCO + emission, which would indicate differences in the physical properties and chemistry within the cloud.